Influence of FCAW process parameters in super duplex stainless steel claddings. (2020) - Kumar, G. Sathish; Saravanan, S.; Balan, A.V.; Oscar, J.; Ragunath, R.; Ramesh, M.
Abstract: Flux cored arc welding (FCAW) is preferred in cladding process due to its augmented efficiency and higher deposition rate. In this research work, to investigate the interaction effect between process parameters of flux cored arc welding on hardness and bead geometry of cladded plate on super duplex stainless steel. The hardness values got increased for the maximum wire feed rate and maximum welding speed, this is due to the dilution rate of the feed wire and also the bead width and bead height got improves for the minimum wire feed rate and minimum welding speed.